Analisis Kolaborasi Guru dan Orang Tua dalam Menindaklanjuti Hasil Asesmen Observasi terhadap Pengembangan Regulasi Diri Anak Usia Dini - Auliya Abd Rahman; Annisa Fahmi Mannassai; Nurain Adwiyah Arif; Siti Khairin Nisa Ismail; Gracia Aulianza Puluhulawa (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study aims to analyze the forms of collaboration between teachers and parents in following up on the results of observational assessments of early childhood self-regulation development. The study employs a qualitative approach with a case study design in a non-formal early childhood education (PAUD) setting. Data were collected through observation, interviews, and analysis of assessment documents. The findings indicate that observational assessment serves as an initial foundation for identifying children’s abilities to manage emotions and behavior. The assessment results are then followed up through collaborative practices in the form of regular communication, exchange of information regarding children’s development, and agreements on guidance strategies between teachers and parents. The role of parents is evident in the consistent implementation of guidance strategies at home, aligned with the stimulation provided by teachers at school. This alignment of roles has been shown to strengthen children’s self-regulation development, particularly in impulse control, behavioral regulation, and the ability to follow rules. The study emphasizes that structured and continuous teacher–parent collaboration is a key factor in the effectiveness of follow-up actions based on observational assessment results in supporting early childhood social-emotional development.